Using the concept of energy of a simple pendulum to illustrate problem solving - Academia, Felino Mac Aurea 1927- (s.n.], 1967)
This paper intends to show that problem solving as an objective in physics (science) teaching is not simply mathematical in nature. Furthermore, this paper illustrates experiments in physics, which though involving subtle and significant principles, can be done using simple apparati like the pendulum and the timer. Moreover, this illustrates problem solving as a composite of many skills of varying degrees of complexity, and presents certain aspects of problem solving.